2018
DOI: 10.1016/j.ergon.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of human body vibration exposures on haul trucks operating at U.S. surface mines/quarries relative to haul truck activity

Abstract: Workers who operate mine haul trucks are exposed to whole-body vibration (WBV) on a routine basis. Researchers from the National Institute for Occupational Safety and Health (NIOSH) Pittsburgh Mining Research Division (PMRD) investigated WBV and hand-arm vibration (HAV) exposures for mine/quarry haul truck drivers in relation to the haul truck activities of dumping, loading, and traveling with and without a load. The findings show that WBV measures in weighted root-mean-square accelerations (aw) and vibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Mayton et al investigated the exposure to human vibration among haul trucks operators. They reported that some haul truck drivers exposed to WBV higher than the ELV according the ISO recommendation (Mayton et al, 2018). In a cross‐sectional study, WBV in graders, bulldozers, and drill machines were reported about 2.791, 1.738 , and 0.479 m/s 2 , respectively so that the human vibration in most mining machines is higher than the recommended levels (HashemiNejad et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mayton et al investigated the exposure to human vibration among haul trucks operators. They reported that some haul truck drivers exposed to WBV higher than the ELV according the ISO recommendation (Mayton et al, 2018). In a cross‐sectional study, WBV in graders, bulldozers, and drill machines were reported about 2.791, 1.738 , and 0.479 m/s 2 , respectively so that the human vibration in most mining machines is higher than the recommended levels (HashemiNejad et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body vibration (WBV) and hand-arm vibration exposures were measured for seven drivers from four different surface quarry mine sites (2 limestone, 1 sandstone, 1 copper). Mayton et al (2016) provide detailed findings of the exposure levels, but overall many of the measurements were below consensus standards with the exception of two mine sites where haul roads were rougher and led to higher vibration levels. Whole-body vibration levels were also higher when the trucks were traveling empty compared to traveling while loaded.…”
Section: Methods and Findingsmentioning
confidence: 98%
“…The authors emphasized the discrepancy between the two standards. Mayton, Jobes, and Miller (2008) and Mayton et al (2018) found that old trucks gave higher vibration values, with the vibration acceleration in the Z-axis being dominant. An evaluation of the WBV and GPS position data revealed that most of the shocks occurred during loading and unloading, and from the potholes in the road.…”
Section: Introductionmentioning
confidence: 99%